Briquetes produzidos com mistura de podas urbanas, glicerina e resíduos de processamento de mandioca - Petricoski, Silvia Maccari (2017)
Throughout history, several sources and forms of energy have been used for production of goods and services. especially energy generated from fossil fuels such as oil. Due to the limits of their world reserves; CO2 emissions and ecological disasters from oil well drilling, it is crucial to think in renewable and sustainable sources of energy: those that naturally reconstitute themselves in a short period of time. One the alternatives for solving this problem is the energy coming from biomasses, whether animal or vegetable origin, it can be used to production of energy. The briquette is considered a solid biofuel, made from compaction of lignocellulosic residues much used to energy generation. This paper aimed to study production of briquettes from mixtures of urban pruning waste - RPU, from glycerine and cassava bagasse (Manihot esculenta). A prototype drier was used through solar heating to reduce humidity of RPU and cassava samples. Afterwards, samples of RPU, cassava bagasse and glycerin were mixed, yielding the treatments T1 (100% RPU), T2 (92% RPU and 8% Cassava bagasse), T3 (97% RPU and 3% Glycerin), T4 (89% RPU, 8% Cassava bagasse and 3% Glycerin) and T5 (94.5% RPU, 4% Cassava bagasse and 1,5% Glycerin). Then the analyzes of physical, chemical and energetic parameters the briquettes were carried out. The moisture content of the briquettes was lower in T1 treatment (7.935%). T2 treatment had lower fixed carbon value (16.858%) volatile content (66.520%) and higher ash content (16.621%). The percentages of C, H and N did not differ statistically between the treatments. The values of the upper, lower and useful calorific value were higher on T3 (18.973 MJ kg-1); (17,480 MJ kg-1) and (15,980 MJ kg-1) respectively. The apparent density was higher in T1 (1183 kg m-3) as well as energy density (20778.76 MJ m-3). Treatment T2 had the highest mechanical strength (1,281 kgf cm-2). The results, therefore, showed that treatments T1, T2 and T3 were more efficient, producing briquettes with properties that meet specifications of the market, besides presenting great energetic potential, being good substitutes for firewood. Based on information collected in Vera Cruz do Oeste - PR in 2015, approximately 76.92 t ano-1 of briquettes from urban pruning residues could be produced, thus contributing to generation of revenue in the value of R$ 23,614.44.